Biogenic Waste from Two Varieties of Plantain in Ghana Contain Pectin with Potential Binding Properties in Conventional Tablets - Desmond Asamoah Bruce Otu; Frederick William Akuffo Owusu; Mariam El Boakye-Gyasi; Raphael Johnson; Prince George Jnr Acquah; Yayra Edzor-Agbo; Marcel Tunkumgnen Bayor; Mary-Ann Archer (The Scientific World Journal)
Pharmaceutical formulations have traditionally relied on plants and their derivatives for various APIs and excipients. In Ghana, the widespread utilization of plantains, irrespective of their ripeness, generates significant waste at every stage of processing, posing disposal issues. Fascinatingly, these wastes, often discarded, possess significant economic potential and can be recycled into valuable raw materials or products. Pectin, a polysaccharide that occurs naturally, has seen a surge in interest in recent times. It has found widespread use in the pharmaceutical sector, particularly as a binding agent in tablet formulations. This study aimed to evaluate pectin from two popular plantain varieties, Apem (M) and Apantu (T) at different ripening stages, for pharmaceutical use as a binding agent in immediate-release tablets. The ripening stages selected were the matured-green (G), half-ripe (H), and full-ripe (R). Acid (D) and alkaline (L) mediums of extraction were employed for each ripening stage for both varieties. Wet granulation method was used to prepare the granules using paracetamol as a model drug, and their flow properties were subsequently assessed. Postcompression tests including, hardness, friability, weight uniformity, disintegration, assay, and in vitro dissolution were also assessed. Granules from all formulation batches had good flow properties indicated by their angle of repose (14.93 ± 1.41–21.80 ± 1.41), Hausner ratio (0.96 ± 0.27–1.22 ± 0.02), and compressibility (%) (7.69 ± 0.002–20.51 ± 0.002). All the tablets passed the uniformity of weight with none deviating by ±5%. The hardness of all the formulated tablets ranged between 3.96 ± 0.32 and 13.21 ± 0.36, while the friability for all tablets was below 1%. The drug content was between 100.1 ± 0.23% and 103.4 ± 0.01%. Tablets formulated with pectin as a binding agent at concentrations of 10% w/v and 15% w/v successfully met the disintegration test criteria for immediate release tablets. However, those prepared with a concentration of 20% w/v (MGL, MHD, MHL, MRD, MRL, TGL, THD, THL, and TRL) did not pass the disintegration test. Consequently, all batches of tablets successfully met the dissolution test requirement (Diss, Q > 75%), except for the batches that did not pass the disintegration test (Diss, Q < 75%). Ultimately, pectins extracted from the peels of Apem and Apantu at different ripening stages using acid and alkaline extraction can be commercially exploited as pharmaceutical binders at varying concentrations in immediate-release tablets.